Autogestão e tecnologia em cooperativa de catadores/as de resíduo: uma análise intersubjetiva sob a óptica do campo ciência, tecnologia e sociedade - Franceschini, Guilherme (Universidade Federal de São Carlos, 2011)
The current society presents sharp inequalities, based on competition and individualistic values. Aiming to break up with such values which result in unemployment, poor working conditions and social exclusion, the solidarity economy brings elements such as solidarity, cooperation, self-management. Given this reality, we highlighted a class of informal workers, called waste pickers , responsible for collecting about 90% of the waste directed to recycling plants in Brazil. Besides having a role in the economy, the waste pickers have specific knowledge and skills necessary to identify, collect, sort, add value and sell that waste. This case study, focused on the Coopervida, a waste pickers cooperative of São Carlos-SP, adopted a qualitative approach and intended to identify according to the view of the waste pickers, what elements are transformers and what are obstacles for the autonomy in the work of the Cooperative, with a focus on self-management, the development of social technologies and on the process of socio-technical adequacy. According with the referenced theory in science and technology, the critical communicative methodology was used, with the realization of communicative groups as a technique for collecting primary data. The interaction between the researcher and the research subjects (one male and two female members of the cooperative) happened through the establishment of an intersubjective dialogue in which they participated from the point of defining the research question to the data analysis. As one of the results achieved we identified as the main transforming element, the recognition by the workers of the importance of cooperation, solidarity, participation in the activities of formation and adding value to waste to the self-management practices and the advance towards the Cooperative autonomy. The workers development of social technologies and the socio-technical adequacy process was also found to be an important transforming element for the autonomy in the work of Coopervida. In contrast, the lack of cooperation of some workers, the sometimes truncated communication between them, along with the difficulty in breaking up with the division of manual and intellectual work, expressed in the dichotomy between production and management, are the main obstacles to the Cooperative autonomy, since such actions are not directed towards the values of self-management that the venture is proposing to accomplish. We related the themes investigated with Science, Technology and Society field, through the participation of the research subjects in the production of knowledge and in the adequation of technologies with the objective of overcoming social inequality and in favor of the historically marginalized classes.
Keywords: Desenvolvimento social - ciência, tecnologia e sociedade; Cooperativas de catadores de resíduos; Economia solidária; Autogestão no trabalho; Adequação sóciotécnica; Tecnologia social; Cooperatives of waste pickers; Solidarity economy; Science, technology and society; Social technology; Social and technical adequacy; Self management; CIENCIAS SOCIAIS APLICADAS